MENILIK MODAL SIMBOLIK HALIMI ZUHDY SEBAGAI SASTRAWAN ARAB DARI INDONESIA - Milal, Mukhamad Syaiful (Sunan Kalijaga State Islamic University Yogyakarta, 2021)
This research aims to disclose the symbolic capital of Halimi Zuhdy as an Arabic Poet of Indonesian. Halimi's legitimacy cannot be separated from the symbolic, social and cultural capital he possesses. This research scrutinizes the strategy and legitimacy of Halimi as an Arab Poet from Indonesia. To describe this problem, the researcher uses the literary sociology approach of Pierre Bourdieu, especially concerning the arena of literary production and legitimacy in gaining symbolic capital. Halimi has practical social capital as he was educated at an Islamic boarding school. At the same time, institutionally, Halimi is a caregiver for the Darunnun Islamic boarding school. In Halimi's cultural capital, he has written several Arabic literary works and he has achieved a position as Chair of the Arabic Language and Literature study program and a new position of Deputy Dean the Faculty of Humanities UIN Malang. Meanwhile, in terms of symbolic capital, Halimi was nominated for the Nobel Prize in Literature from Munir Mazid for his achievements. The accumulation of capital built up in the literary arena has made Halimi achieve the position of an Indonesian Arab Poet. The dialectic of knowledge built by Halimi has also accumulated his fame.